2016
DOI: 10.1002/2016gl071540
|View full text |Cite
|
Sign up to set email alerts
|

Strain‐induced permeability increase in volcanic rock

Abstract: The extrusion of dense, viscous magma typically occurs along pronounced conduit‐parallel faults. To better understand the evolution of fault permeability with increasing strain, we measured the permeability of low‐porosity volcanic rock samples (basalt and andesite) that were deformed in the brittle regime to various levels of inelastic strain. We observed a progressive increase in sample permeability with increasing inelastic strain (i.e., with continued sliding on the fault plane). At the maximum imposed ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 50 publications
1
33
0
Order By: Relevance
“…1b). In volcanic rock -at the sample scale -this is characterised by significant shortening and barrelling of the sample (a consequence of the high strains required to achieve and exceed C * ) and the generation of a dilatant shear zone (Heap et al, 2015a), characteristically similar to highly strained fault zones observed in volcanic rock (Farquharson et al, 2016b). Figure 4 illustrates these separate mechanisms, with evidence of cataclastic pore collapse being shown in Fig.…”
Section: A Limit To Compaction and Permeability Reductionmentioning
confidence: 98%
See 4 more Smart Citations
“…1b). In volcanic rock -at the sample scale -this is characterised by significant shortening and barrelling of the sample (a consequence of the high strains required to achieve and exceed C * ) and the generation of a dilatant shear zone (Heap et al, 2015a), characteristically similar to highly strained fault zones observed in volcanic rock (Farquharson et al, 2016b). Figure 4 illustrates these separate mechanisms, with evidence of cataclastic pore collapse being shown in Fig.…”
Section: A Limit To Compaction and Permeability Reductionmentioning
confidence: 98%
“…7 and suggests that for a volcanic rock of given initial porosity, there is a limited range of strain-induced subsolidus k-φ states in which it can exist: one cannot compact indefinitely without promoting dilatant mechanisms. Figure 7 compiles data from this study with those of Farquharson et al (2016b) and Heap et al (2015a). Farquharson et al (2016b) performed triaxial experiments on lowand intermediate-porosity volcanic rocks (basalt from Mount Etna, Italy, and andesites from Volcán de Colima and Kumamoto, Japan), exploring the evolution of physical properties as a function of stress-induced dilation.…”
Section: A Limit To Compaction and Permeability Reductionmentioning
confidence: 99%
See 3 more Smart Citations